The Experience of Being: Toward an Affective Reduction in Martin Heidegger - Octavian Ioniță, Chris (Laval théologique et philosophique, 2026)
In this article, I intend to address what Heidegger repeatedly names — without fully thematizing — Erfahrung, which I read here in connection with the Erlebnis of the phenomenological tradition and thus in continuity with a philosophical project aimed at returning to the “things themselves.” More precisely, however, I argue that this encounter with things (Dinge), rather than with their representations (Gegenstände, Vorstellungen), while reducing to the immanence of experience those objects that would otherwise transcend it, does not amount to a transcendental reduction but instead proceeds from an affective one. Namely, it is the process of appropriation and transformation that, pivoting on our attunement (Stimmung) to being itself, brings both us and things back to the “da” of our Da-sein, wherein phenomenality eventuates (ereignen).